(untitled) (Journal of Bio-Science, 2023)
Petroleum ether (pet. ether), chloroform (CHCl3) and methanol (CH3OH) extracts of Petunia integrifolia (Hook.) Schinz & Thell. Whole plant was subjected to assess cytotoxicity against the brine shrimp Artemia salina L. nauplii, larvicidal activity against the mosquito Culex quinquefasciatus Say larvae and piscicidal activity against the Poecilia reticulata Peters adults. The P. integrifolia extract in pet. ether showed the highest cytotoxic activity against A. salina nauplii by giving the minimum LC50 value of 49.25 parts per million (ppm) at 48 h, while in case of CHCl3 and CH3OH extracts, the values were 63.37 and 342.55 ppm, respectively. Against C. quinquefasciatus larvae the three extracts gave LC50 values of 4.92, 5.51 and171.26 ppm, respectively all after 48 h of exposure. Against P. reticulata the LC50 values were 21.70 ppm for pet. ether extract at 48 h, and 31.91 ppm for CHCl3 extract after 42 h of exposure but CH3OH extract offered no mortality. According to the intensity of activity, therefore, the extracts could be arranged in the descending order of: pet. ether > CHCl3 > CH3OH extracts; and the sensitivity of the test organisms to the extract of P. integrifolia could be arranged in the following descending order: C. quinquefasciatus larvae (in Pet. ether; LC50 = 4.92 ppm) > P. reticulata (in pet ether; LC50 = 21.70 ppm) >A. salina nauplii (in pet. ether; LC50 = 49.25 ppm) J. Bio-Sci. 31(1): 99-108, 2023